Synthesis and Evaluation of In Vitro Antibacterial and Antitumor Activities of Novel N,N-Disubstituted Schiff Bases - Heng Luo; Yu-fen Xia; Bao-fei Sun; Li-rong Huang; Xing-hui Wang; Hua-yong Lou; Xu-hui Zhu; Wei-dong Pan; Xiao-dong Zhang (Biochemistry Research International)
To get inside the properties of N,N-disubstituted Schiff bases, we synthesized three high-yielding benzaldehyde Schiff bases. We used the reaction between salicylaldehyde and different diamine compounds, including diamine, ethanediamine, and o-phenylenediamine, determining the structure of obtained molecules by nuclear magnetic resonance spectroscopy and electrospray ionization mass spectroscopy. We thus evaluated the microbicidal and antitumor activity of these compounds, showing that salicylaldehyde-hydrazine hydrate Schiff base (compound 1a) significantly inhibited the growth of S. aureus; salicylaldehyde-o-phenylenediamine Schiff base (compound 1c) displayed a strong capability to inhibit the proliferation of leukemia cell lines K562 and HEL. Moreover, we observed that the antibacterial action of 1a might be associated with the regulation of the expression of key virulence genes in S. aureus. Compound 1c resulted in a strong apoptotic activity against leukemia cells, also affecting the cell cycle distribution. Overall, our novel N,N-disubstituted Schiff bases possess unique antibacterial or antitumor activities that exhibit the potent application prospect in prophylactic or therapeutic interventions, providing new insights for developing new antibacterial and anticancer chemical agents.